Quantification of the effect of GLP‐1R agonists on body weight using in vitro efficacy information: An extension of the Hall body composition model - Rolien Bosch; Eric J. G. Sijbrands; Nelleke Snelder (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Obesity has become a major public health concern worldwide. Pharmacological interventions with the glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) have shown promising results in facilitating weight loss and improving metabolic outcomes in individuals with obesity. Quantifying drug effects of GLP‐1RAs on energy intake (EI) and body weight (BW) using a QSP modeling approach can further increase the mechanistic understanding of these effects, and support obesity drug development. An extensive literature‐based dataset was created, including data from several diet, liraglutide and semaglutide studies and their effects on BW and related parameters. The Hall body composition model was used to quantify and predict effects on EI. The model was extended with (1) a lifestyle change/placebo effect on EI, (2) a weight loss effect on activity for the studies that included weight management support, and (3) a GLP‐1R agonistic effect using in vitro potency efficacy information. The estimated reduction in EI of clinically relevant dosages of semaglutide (2.4 mg) and liraglutide (3.0 mg) was 34.5% and 13.0%, respectively. The model adequately described the resulting change in BW over time. At 20 weeks the change in BW was estimated to be −17% for 2.4 mg semaglutide and −8% for 3 mg liraglutide, respectively. External validation showed the model was able to predict the effect of semaglutide on BW in the STEP 1 study. The GLP‐1RA body composition model can be used to quantify and predict the effect of novel GLP‐1R agonists on BW and changes in underlying processes using early in vitro efficacy information.